The Knowledge and Attitudes Relations Elderly With Elderly Participation In Urban SembungharjoKota IHC Elderly In Semarang - Fitriani Nur Damayanti (Jurnal LINK, 2012)
IHC is a form of health care organized by the community, for the community, with technical support from health professionals. This research community midwifery by using a cross sectional survey and the type of research with a population of 349 elderly. Data collected in this study were primary data by interviewing the questionnaire. Data processed by step editing, scoring, coding, recode and data analysis. Univariate analysis variable distributed with respective proportions, while in the bivariate analyzes with chi square test.